2019
DOI: 10.4149/neo_2019_190107n26
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the 8th edition of the American Joint Committee on Cancer (AJCC) staging system in triple-negative breast cancer

Abstract: The American Joint Committee on Cancer (AJCC) released its 8th edition of cancer staging implemented in early 2018. This study aims to compare anatomic staging (AS) with prognostic staging (PS) based on the updated AJCC 8th edition staging manual. A retrospective single-center analysis of 313 triple-negative breast invasive ductal carcinoma patients who received surgery at department of breast surgery in the Fourth Hospital of Hebei Medical University from 01/2010-12/2012 was performed. All cases were restaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…These findings are consistent with previous study by Liu, et al [8]. On the contrary, contradictory studies by Li, et al [7] and Luo, et al [19] indicated that the PS system displayed a more optimistic prognostic stratification and predictability than traditional AS system. However, Li, et al [7] applied a earlier version of AJCC 8th criterion without subsequent corrections in a small sample cohort including stage IV disease.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with previous study by Liu, et al [8]. On the contrary, contradictory studies by Li, et al [7] and Luo, et al [19] indicated that the PS system displayed a more optimistic prognostic stratification and predictability than traditional AS system. However, Li, et al [7] applied a earlier version of AJCC 8th criterion without subsequent corrections in a small sample cohort including stage IV disease.…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, contradictory studies by Li, et al [7] and Luo, et al [19] indicated that the PS system displayed a more optimistic prognostic stratification and predictability than traditional AS system. However, Li, et al [7] applied a earlier version of AJCC 8th criterion without subsequent corrections in a small sample cohort including stage IV disease. They also excluded special types of invasive breast cancer, and no relevant statistical methods had been applied to further assess and compare prognostic ability of the two staging systems.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Currently, studies assessing the new AJCC prognostic staging for the TNBC cohort came to conflict results [18e21]. Li et al [19] and Luo et al [21] claimed that the new prognostic staging of AJCC could predict the prognosis of TNBC patients more accurately than the traditional anatomic staging. However, Li et al [19] did not use the corresponding statistical analyses to further assess the prognostic abilities of the two staging systems.…”
Section: Tnbc Is a Specific Subtype Of Bc [24e26] In This Study Wementioning
confidence: 99%
“…Li et al [19] and Luo et al [21] claimed that the new prognostic staging of AJCC could predict the prognosis of TNBC patients more accurately than the traditional anatomic staging. However, Li et al [19] did not use the corresponding statistical analyses to further assess the prognostic abilities of the two staging systems. In addition, Luo et al [21] also acknowledged that the two competing stage systems (the new AJCC prognostic staging vs. traditional TNM staging) did not have significant differences in AUC values.…”
Section: Tnbc Is a Specific Subtype Of Bc [24e26] In This Study Wementioning
confidence: 99%